Zippers with resin injection molded components, and garments using them.
Patent Information
- Application Number
- TW114122560
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-14
- Filing Date
- 2025-06-17
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2045-06-16
AI Technical Summary
The use of polyethylene terephthalate (PET) resin in injection-molded zipper components is hindered by poor mold filling, mold release issues, insufficient crystallization, and manufacturing inefficiencies due to high-temperature molds, leading to deformation and discoloration under high-temperature washing conditions, which limits its practical application in zippers.
Incorporating a crystallizing nucleating agent, antioxidants, and lubricants into the PET resin to enhance crystallinity and stability, allowing for PET resin injection molding at lower temperatures and maintaining functional integrity under high-temperature conditions.
The solution enables the use of recycled PET resin in zipper components with improved crystallinity, preventing deformation and discoloration, ensuring the zipper's functionality and appearance even under high-temperature washing and drying conditions.
Smart Images

Figure TWG2TA001076169_001 
Figure TWG2TA001076169_002 
Figure TWG2TA001076169_003
Abstract
Description
[Technical Field]
[0001] This invention relates to a zipper in which any of the components of a zipper are manufactured by resin injection molding. In particular, it relates to a zipper having an injection-molded component, wherein, in terms of the resin material, polyethylene terephthalate (PET), which is not readily practical, is used as the material for general-purpose products that have been mass-produced in the zipper industry to date. [Previous Technology]
[0002] Since then, it has been widely carried out to manufacture zipper teeth, stops, and opening parts as components of zippers by resin injection molding. Figures 1 and 2 are diagrams showing the general shape of such zippers.
[0003] As shown in Figure 1, regarding the zipper 70, a plurality of chain teeth 73 are integrally installed on the edge side of one side of the zipper tape 71 and zipper tape 72 by resin injection molding. Furthermore, an upper stop 74 is installed at the upper end of the plurality of chain teeth 73, and a lower stop 75 is installed at the lower end. The upper stop 74 and lower stop 75 are also integrally installed on the zipper tape 71 and zipper tape 72 by resin injection molding. The engagement of the chain teeth 73 is achieved by the up-and-down operation of the zipper head 76, on which a pull tab 77 for operation is installed.
[0004] Figure 2 is another example of a zipper having a component manufactured by resin injection molding, and it shows a type of zipper that includes an opening member instead of the lower stop 75 in Figure 1. Figure 2 only shows the structure around the opening member, which includes a push bar 93 and a socket 94. The socket 94 has a base 95 and a push bar 96 that extends from the base 95 toward the zipper tooth 73. The base 95 has a push bar hole 93a that serves as a space for the push bar 93 to be inserted. In addition, the base 95 has a groove 91a, and the two sides of the groove 91a are flanges 95a. In addition, a resin film 97 is provided on the surface of the zipper tape 91 and zipper tape 92 adjacent to the push bar 93 and the socket 94. The resin film 97 is provided to enhance the zipper for the purpose of facilitating the operation of the opening parts of the zipper. It may include, for example, a polyamide film, a polyester film, a polyolefin film, or a polyurethane film, and is installed on the zipper tape 91 and zipper tape 92 by bonding or heat fusion.
[0005] In the case of resin injection molding of zipper chain teeth 73, upper stop stopper 74, lower stop stopper 75, plug rod 93, socket 94, etc., which are the components of the zipper, polyformaldehyde (polyformaldehyde (POM)) is desirable for useful material applications in terms of resin materials. Polyacetal is a resin material with excellent strength, abrasion resistance, and heat resistance, and is also excellent as a material for injection molding in the mold. Therefore, as a resin material used in resin injection formed parts of mass-produced general-purpose zippers, polyacetal is generally used. [Existing technical literature] [Patent literature]
[0006] Patent Literature 1: Japanese Patent Publication No. 10-243805 Bulletin Patent Literature 2: Chinese Patent Publication No. 111925632 Bulletin Patent Literature 3: Japanese Patent Publication No. 2003-138114 [Invention Contents]
[0007] [The topic to be solved by the invention] In recent years, awareness devoted to sustainable development activities has increased throughout the industrial field, but in the field of zippers, the development of such products with consideration of the environment has been attempted since before, for example, in the patent literature Furthermore, the zipper described as an embodiment of the patent literature 1 does not pertain to a chain teeth subjected to resin ejection forming, but to a nylon zipper in which extrusion-formed monofilament is used as chain teeth, in particular polyethylene terephthalate (PET) after recirculation realized efficiently utilized as a recycled material. As a recycling material for resins, PET is a material present in large quantities on the market and is further required to be recycled. Regarding the use of the PET as a material use for a zipper, as noted in the patent literature 1 , as a monofilament used for extrusion forming has been practical as a universal article, but as an ejection-formed component for use in chain teeth, stop stoppers, and open pieces of the zipper. As a reason for the inability to be practical, a large reason is that PET is an unsuitable material for resin injection forming in the mold.
[0008] Specifically, if PET is injection molded in a mold previously used for injection molding of zipper injection molding components, i.e., a mold used for injection molding of polyacetal resin, defects such as poor filling or poor mold release become significant. Furthermore, because the PET resin is rapidly cooled, it also becomes unable to crystallize sufficiently. Therefore, when using PET as the material for injection molding components of zippers, a mold heated to a high temperature is used. Such use of a mold heated to a high temperature is described, for example, in Patent Documents 2 and 3.
[0009] Paragraph 0038 of Patent Document 2 describes an injection molding mold temperature of 80°C, 50°C, or 60°C, and claim 4 of Patent Document 2 describes an injection molding mold temperature of 30°C to 85°C. Furthermore, paragraph 0015 of Patent Document 3 describes an injection molding mold temperature preferably in the range of 30°C to 60°C or 120°C to 150°C. By using high-temperature molds as described in Patent Documents 2 and 3, some of the defects in PET resin injection molding within the mold are eliminated. However, the use of high-temperature molds creates another new problem that significantly reduces manufacturing efficiency. That is, the time required from injecting PET resin to opening the mold and removing the product is significantly longer than before, thus creating another problem of significantly reduced manufacturing efficiency. Additionally, as another problem, when the zipper is the type shown in Figure 2, including an opening mechanism, there is a problem of easy formation of a cloudy resin film 97. That is, when the insert 93, socket 94 and seat 96 are injection molded into the zipper tape 91 and zipper tape 92 which are provided with resin film 97, if the temperature of the mold becomes high, excessive heat will be applied to the resin film 97 under the pressure generated by the mold, and the resin film 97 will become cloudy.
[0010] Furthermore, in Patent Documents 2 and 3, a value of 30 degrees Celsius is described as the lower limit of the temperature range for high-temperature molds. However, in practice, when injection molding is performed within this relatively low mold temperature range, poor filling or poor mold release is not adequately improved. Additionally, insufficient crystallization of the resin in the extracted product is also a problem. In particular, in regions where washing and drying are typically done at high temperatures, the problem of insufficient resin crystallization becomes a significant issue when using garments with this zipper. For example, in Europe, washing and drying are often done at temperatures above 90 degrees Celsius or above 120 degrees Celsius. If a zipper with insufficient resin crystallization is exposed to such high-temperature washing and drying conditions, the injection-molded part deforms, and sometimes the zipper's original opening and closing function cannot be performed.
[0011] The purpose of this application is to provide a zipper that solves several issues related to this complex relationship; thereby, PET resin can be used as a more versatile material for the resin injection molded component of the zipper. This objective achieves both the widespread use of recycled PET resin as a zipper material and the social requirement to respond to sustainable development activities.
[0012] Furthermore, the inventors of this application conducted research in pursuit of the aforementioned objective and discovered that when a certain type of antioxidant is used during injection molding, a noticeable discoloration of the manufactured resin molded parts to gray occurs. Moreover, the inventors of this application also learned that if a certain substance is mixed into the PET resin, this gray discoloration can be suppressed. Therefore, one of the objectives of this application is to provide a method that can suppress the graying of PET resin injection molded parts even when combined with an antioxidant. By achieving this additional objective, the main objective of practically using PET materials in resin injection molded parts for zippers can be achieved more generally. [Means for Solving the Problem]
[0013] In order to achieve the above-mentioned objective, the present invention has the following features.
[0014] The zipper of the present invention is a zipper with teeth installed on the edge of the zipper tape. The zipper has a resin injection part formed by injection molding a synthetic resin containing polyethylene terephthalate as the main component onto the zipper tape. The synthetic resin of the resin injection part contains a crystallizing nucleating agent, and the degree of crystallinity of the resin injection part is 12% or more.
[0015] Preferably, the resin injection component is any one or a combination of any number of zipper teeth, lower stop, upper stop, insert, and socket.
[0016] In addition, preferably, the resin injection component is a plug or socket, and a resin film is provided on the zipper tape adjacent to the plug or socket.
[0017] In addition, preferably, the resin injection component is a component manufactured by injection into a mold at a temperature of less than 30°C.
[0018] In addition, preferably, the resin injection component is a component made of a synthetic resin that does not become a combination of polyethylene terephthalate resin using antimony as a polymerization catalyst, phosphorus-based antioxidants, and crystal nucleating agents.
[0019] Furthermore, the zipper of the present invention is a zipper with teeth installed on the edge of the zipper tape. The zipper has a resin injection component formed by injection molding a synthetic resin containing polyethylene terephthalate as the main component onto the zipper tape. When the total amount of synthetic resin in the resin injection component is set to 100% by weight, the synthetic resin contains more than 50 ppm of phosphorus and more than 20 ppm of calcium.
[0020] Preferably, the synthetic resin contains a lubricant containing calcium.
[0021] In addition, preferably, the polyethylene terephthalate, which is the synthetic resin, comprises recycled polyethylene terephthalate.
[0022] In addition, a garment using the zipper of the present invention is capable of being washed at high temperatures above 90°C.
Implementation Method
[0023] Hereinafter, embodiments of the present invention will also be described with reference to the drawings. Furthermore, the present invention is not limited to the embodiments described below. Additionally, descriptions of structures or functions that are repeated between embodiments are generally omitted.
[0024] FIG1 is a diagram previously used in the prior art, showing the general form of a zipper having components manufactured by resin injection molding, but it also shows the appearance of the zipper in the embodiment of the present invention. FIG2 is also a diagram showing the general form of a zipper (a zipper with an opening member) having components manufactured by resin injection molding, and it shows the appearance of the zipper (a zipper with an opening member) in the embodiment of the present invention. Thus, the embodiment of the zipper in the present invention is implemented with the same appearance as the previous zippers in terms of component appearance. Therefore, since the names and functions of the components shown in FIG1 and FIG2 are the same as those already described in the prior art, further explanation is omitted. In FIG1, the zipper 70 is illustrated as an example where the chain teeth 73, upper stop 74, and lower stop 75 are all formed by resin injection molding. Incidentally, a zipper 70 formed by resin injection molding of only any one of the chain teeth 73, upper stop 74, and lower stop 75 is also included within the scope of the embodiments of the present invention. Similarly, in FIG2, an example is illustrated where the insert 93, socket 94, and chain teeth 73 are all formed by resin injection molding. Incidentally, a zipper 70 formed by resin injection molding of only any one of the insert 93, socket 94, and chain teeth 73 is also included within the scope of the embodiments of the present invention.
[0025] (Resin Injection Molding Component) The resin injection molding component of this embodiment is manufactured from a synthetic resin containing polyethylene terephthalate as a main component. Here, "containing polyethylene terephthalate as a main component" means a resin containing 50% or more polyethylene terephthalate relative to the total weight percentage of the synthetic resin, preferably defined as containing 80% or more of the resin. The resin injection molding component of this embodiment contains (A) resin, (B) a crystallizing nucleating agent, (C) an antioxidant, (D) a lubricant, and (E) pigment as main components. In addition, the proportions of (A), (B), (C), (D), and (E) are 85% or more and 99% or less, 0.1% or more and 3.0% or less, 0.35% or more and 5.0% or less, 0.1% or more and 3.0% or less, and 0.1% or more and 10% or less, respectively. Furthermore, since the pigment (E) is added for coloring purposes, it is sometimes not included when coloring is not required. In particular, in the test examples described below, there are also examples of parts made into a transparent resin state without intentional coloring, and the physical properties of such parts are evaluated. In addition to the main components (A), (B), (C), (D), and (E) mentioned above, other additives are sometimes added to improve the functionality of the resin material. Hereinafter, the main components (A), (B), (C), (D), and (E) will be described individually.
[0026] (A) Resin) The resin in (A) of this embodiment is mainly PET resin or recycled PET resin. PET generally refers to a resin obtained by heating terephthalic acid or its ester-forming derivatives (e.g., dimethyl ester, monomethyl ester, and other lower alkyl esters) and ethylene glycol or its ester-forming derivatives in the presence of a catalyst, thereby polymerizing the resulting glycol ester of terephthalic acid to a predetermined degree of polymerization in the presence of a catalyst. Recycled PET resin in this invention refers to a resin that is recycled and processed after the PET has been molded into large molded articles such as beverage bottles, fibers, films, or containers, for reuse; this is commonly referred to as recycled PET material or recycled PET. The PET resin used in this invention is not limited to the product form of the recycled PET; specifically, it can be resins recycled from beverage bottles, fibers, films, molded articles, etc. Furthermore, even if not actually used as an article, it can be PET resin used for end materials of films produced during article manufacturing, gates and runner components of injection molded articles, etc. Sometimes, other resin materials are added to PET resin to improve functionality, but the weight percentage of other resin materials will not exceed the weight of PET resin.
[0027] (B) Crystallization nucleating agent) The (B) crystallization nucleating agent in this embodiment is used to improve heat resistance by increasing the crystallinity of (A) resin. As described above, when PET resin is injection molded into a mold for a previously used zipper injection molding part, i.e., a mold used for injection molding of polyacetal resin at room temperature, the PET resin is rapidly cooled, thus becoming insufficiently crystallized. If it is used as a component of a zipper product in an insufficiently crystallized state, and heat exceeding 70°C to 80°C (the glass transition temperature) is applied during use, the crystallization of the component proceeds due to the heat, resulting in deformation of the component's shape. Previously, attempts were made to increase the crystallinity of the freshly manufactured injection part by raising the temperature of the mold, but in this embodiment, the crystallinity is increased by adding the (B) crystallization nucleating agent. This allows the use of existing molds for zipper injection molding parts. That is, molds that are used and managed at room temperature can continue to be used (in other words, molds used and managed at temperatures below 30°C, or even molds used and managed at temperatures below 20°C). Furthermore, zippers can be manufactured with the same level of efficiency as before. Examples of (B) crystallization nucleating agents include organic and inorganic crystallization nucleating agents. Moreover, these crystallization nucleating agents can be used alone, or two or more can be used.
[0028] Examples of organic crystal nucleating agents include: sodium benzoate, potassium benzoate, lithium benzoate, calcium benzoate, magnesium benzoate, barium benzoate, lithium terephthalate, sodium terephthalate, potassium terephthalate, sodium benzoate, sodium salicylate, potassium salicylate, zinc salicylate, aluminum dibenzoate, potassium dibenzoate, lithium dibenzoate, sodium β-naphthalenedicarboxylate, sodium cyclohexanecarboxylate, and other organic carboxylic acid metal salts; sodium p-toluenesulfonate, sodium sulfoisophthalate, and other organic sulfonates; sorbitol compounds; metal salts of phenylphosphonates; and phosphorus compound metal salts such as sodium-2,2'-methylene bis(4,6-di-tert-butylphenyl) phosphate. Furthermore, these can be used alone or in combination.
[0029] As inorganic crystal nucleating agents, talc, calcium carbonate, mica, boron nitride, synthetic silica, silicates, silica, kaolin, carbon black, zinc oxide, montmorillonite, clay minerals, basic magnesium carbonate, quartz powder, glass fiber, glass powder, diatomaceous earth, dolomite powder, titanium dioxide, zinc oxide, antimony oxide, calcium sulfate, barium sulfate, aluminum oxide, calcium silicate, boron nitride, etc., can be used alone or in combination.
[0030] Relative to 100 parts by weight of resin, the content of (B) crystallizing nucleating agent is typically 0.1 parts by weight to 5 parts by weight, preferably 0.2 parts by weight to 3 parts by weight, and even more preferably 0.3 parts by weight to 1.5 parts by weight. If it is less than 0.1 parts by weight, crystallization will not be promoted, which is undesirable. If it is more than 5 parts by weight, resin deterioration or reduction in physical properties will occur, which is also undesirable.
[0031] (C) Antioxidant) Applying color to zippers is standard practice. The resin injection molding component of the present invention uses PET resin as the base resin. PET resin is heated at high temperatures during processing, etc., and therefore its molecular structure is prone to thermal decomposition. As a result, oxidation or byproducts are formed, causing yellowing. This yellowing may be a major cause of zippers that cannot achieve the desired color. In order to further reduce this yellowing or thermal decomposition of the molecular structure, the resin injection molding component in this embodiment contains an antioxidant. As (C) antioxidant, examples include (C1) primary antioxidant and (C2) secondary antioxidant, preferably using (C1) primary antioxidant and (C2) secondary antioxidant together. In addition, the form of (C) antioxidant can be solid or liquid. As (C1) primary antioxidant, examples include: phenolic antioxidants, hindered phenolic antioxidants, or aromatic amine antioxidants, etc.
[0032] Examples of phenolic antioxidants include: 2,4-dimethyl-6-tert-butylphenol, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol, 2,6-di-tert-butyl-4-ethylphenol, 4,4'-butylidene bis(6-tert-butyl-3-methylphenol), 2,2'-methylene-bis(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis(4-ethyl-6-tert-butylphenol), and 2,4'-methylene-bis(4-ethyl-6-tert-butylphenol). Tributylphenol), octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate, pentaerythritol tetra[3-(3,5-di-tert-butyl-4'-hydroxyphenyl)propionate], 1,1,3-tris(2-methyl-4-hydroxy-5-di-tert-butylphenyl)butane, tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, triethylene glycol bis[3-(3-tert-butyl-4-hydroxy-5'-hydroxyphenyl)] [-methylphenyl)propionate], 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,4-bis-(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylaniline)-1,3,5-triazine, 2,2-thio-diethyl bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexamethylenebis(3,5-di-tert-butyl- Examples of hydroxymethyl cinnamylamine include 3,5-di-tert-butyl-4-hydroxybenzyl phosphate-diethyl ester, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 2,4-bis[(octylthio)methyl]-o-cresol, or isooctyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. Furthermore, these can be used alone or in combination.
[0033] As hindered phenolic antioxidants, examples include: N,N'-hexamethylene-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide, bis(3,3-bis-(4'-hydroxy-3'-tert-butylphenyl)butyrate) glycol ester, 2,1'-thioethyl bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 4,4'-butylene-bis(3-methyl-6-tert-butylphenol), and triethylene glycol-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate ("SONGNOX 2450", molecular weight 633). Furthermore, these can be used alone or in combination.
[0034] Examples of aromatic amine antioxidants include: N-phenyl-1-naphthylamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N,N-diethyl-p-phenylenediamine, N-phenyl-N'-ethyl-2-methyl-p-phenylenediamine, N-ethyl-N-hydroxyethyl-p-phenylenediamine, alkylated diphenylamine, N,N'-diphenyl-p-phenylenediamine, N,N'-diallyl-p-phenylenediamine, N-phenyl-1,3-dimethylbutyl-p-phenylenediamine, 4,4'-dioctyl-diphenylamine, 6-ethoxy-2,2,4-trimethyl-1,2-dihydroxyquinoline, 2,2,4-trimethyl-1,2-dihydroxyquinoline, N-phenyl-β-naphthylamine, and N,N'-di-2-naphthyl-p-phenylenediamine. Furthermore, these can be used alone or in combination.
[0035] As a (C2) secondary antioxidant, phosphorus-based antioxidants or sulfur-based antioxidants can be listed.
[0036] As phosphorus-based antioxidants, examples include: triphenyl phosphite, triisodecyl phosphite, isodeyl diphenyl phosphite, 2-ethylhexyl diphenyl phosphite, 4,4'-isopropylidene diphenylalkyl (C12-C15) phosphite, tri(nonylphenyl) phosphite (Adekastab 1178), tri(2,4-di-tert-butylphenyl) phosphite, 2,2'-methylene bis(4,6-di-tert-butylphenyl)2-ethylhexyl phosphite, 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosspiro[5.5]undecane, 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosspiro[5.5]undecane, etc. Furthermore, these can be used individually or in combination.
[0037] Examples of sulfur-based antioxidants include: dilauryl 3,3'-thiodipropionate, tridecyl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, distearate 3,3'-thiodipropionate, laurylstearyl 3,3'-thiodipropionate, neopentanetetrayltetra(3-lauryl thiopropionate), etc. Furthermore, these can be used alone or in combination.
[0038] Relative to 100 parts by weight of the resin, the content of the (C1) primary antioxidant is typically 0.1 parts by weight to 3 parts by weight, preferably 0.15 parts by weight to 2 parts by weight, and more preferably 0.2 parts by weight to 1 part by weight. Relative to 100 parts by weight of the resin, the content of the (C2) secondary antioxidant is typically 0.1 parts by weight to 5 parts by weight, preferably 0.2 parts by weight to 3 parts by weight, and more preferably 0.3 parts by weight to 1 part by weight. Relative to 100 parts by weight of the resin, the content of both the (C1) primary antioxidant and the (C2) secondary antioxidant is typically 0.2 parts by weight to 8 parts by weight, preferably 0.35 parts by weight to 5 parts by weight, and more preferably 0.5 parts by weight to 2 parts by weight.
[0039] (D) Lubricant) Examples of lubricants include: metal soap-based lubricants, higher fatty acid-based lubricants, ester-based lubricants, and higher alcohol-based lubricants. By using such a lubricant, the viscosity of the composition containing (A) resin, (B) crystallizing nucleating agent, and (C) antioxidant can be reduced, thereby improving formability. Furthermore, it is also effective in controlling the adhesion between the composition and the metal surfaces of the screw, cylinder, die, etc., within the extruder. A single lubricant can be used, or two or more can be used in combination.
[0040] Examples of metal soap-based lubricants include: stearates, laurates, oleates, palmitates, and other metal soaps of Na, Mg, Al, Ca, Ba, etc. Examples of higher fatty acid-based lubricants include: saturated fatty acids such as stearic acid, palmitic acid, myristic acid, lauric acid, and decanoic acid, unsaturated fatty acids such as oleic acid, or mixtures thereof. Examples of ester-based lubricants include: ester-based lubricants containing alcohols and fatty acids; pentaerythritol-based lubricants such as pentaerythritol or dipentaerythritol with higher fatty acids in the form of monoesters, diesters, triesters, tetraesters, or mixtures thereof; and lignite wax-based lubricants containing esters of lignite acid with higher alcohols such as stearyl alcohol, palmitol, myristic alcohol, lauryl alcohol, and oleyl alcohol. Examples of higher alcohol-based lubricants include: stearyl alcohol, palmitol, myristic alcohol, lauryl alcohol, and oleyl alcohol.
[0041] The content of (D) lubricant is usually 0.1 to 5 parts by weight, preferably 0.2 to 3 parts by weight, and more preferably 0.3 to 2 parts by weight, relative to 100 parts by weight of resin.
[0042] (E) Pigments) As pigments, any pigment can be selected according to the desired hue. For example, organic pigments and inorganic pigments can be listed. As inorganic pigments, examples include: silicic acid, silicic anhydride, magnesium silicate, talc, sericite, mica, kaolin, iron oxide, clay, bentonite, titanium-coated mica, bismuth oxychloride, zirconium oxide, magnesium oxide, zinc oxide, titanium oxide, aluminum oxide, calcium sulfate, barium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, iron oxide, ultramarine, chromium oxide, chromium hydroxide, calamine, and complexes thereof. As organic pigments, examples include: polyamide, polyester, polypropylene, polystyrene, polyurethane, vinyl resin, urea resin, phenolic resin, fluororesin, silicone resin, acrylic resin, melamine resin, epoxy resin, polycarbonate resin, divinylbenzene-styrene copolymer, silk powder, cellulose, color index (CI) pigment yellow, CI pigment orange, etc. Furthermore, composite pigments that combine inorganic and organic pigments can also be used.
[0043] The content of pigment (E) is usually 0.01 to 15 parts by weight relative to 100 parts by weight of resin, preferably 0.1 to 10 parts by weight, and even more preferably 0.5 to 7 parts by weight.
[0044] (Manufacturing Method of Resin Injection Part) The zipper manufacturing method in this embodiment involves heating resin granules as the material to melt them, injecting the molten resin into a mold, and integrally forming it with a zipper tape pre-positioned in the mold. This zipper manufacturing method is the same as the previous resin injection zipper manufacturing method, which is known in various existing documents (for example, International Publication No. 2013 / 088561, etc.). Therefore, a detailed description of the zipper manufacturing method itself is omitted. The manufacturing method in this embodiment is characterized in that, while the resin granules as the material are heated to melt them, they are mixed with the main components described above: (A) resin, (B) crystallizing nucleating agent, (C) antioxidant, (D) lubricant, and (E) pigment. These components are preferably pre-mixed into the resin granules themselves. Therefore, it is preferable to pre-manufacture resin granules by mixing (A) resin, (B) nucleating agent, (C) antioxidant, (D) lubricant, and (E) pigment as main components during the resin granule manufacturing stage. Alternatively, another manufacturing method according to this embodiment may be exemplified by: (i) using a method comprising a masterbatch containing (E) pigment and a complex comprising (A) resin, (B) nucleating agent, (C) antioxidant, and (D) lubricant; or (ii) using a method comprising a masterbatch containing (E) pigment and (B) nucleating agent and a complex comprising (A) resin, (C) antioxidant, and (D) lubricant, etc. [Example]
[0045] Hereinafter, embodiments and comparative examples are given to specifically illustrate the present invention, but the present invention is not limited to these examples.
[0046] (Method for Determining the Degree of Crystallinity) The degree of crystallinity was determined based on the method described in Japanese Industrial Standards (JIS) K7122:2012 "Method for Determination of Heat Transfer of Plastics". A differential scanning calorimetry (DSC) curve was obtained using a Hitachi High-Tech Science DSC200 instrument, with approximately 5 mg of the test sample filled in the test data container and heated from 20°C to 300°C at a rate of 10°C / min. The degree of crystallinity was calculated by dividing the difference between the heat of fusion (J / g) calculated from the area of the melting peak and the heat of crystallization (J / g) calculated from the area of the crystallization peak by the theoretical heat of fusion for complete crystallization of polyethylene terephthalate (140.0 J / g in the case of polyethylene terephthalate). The heat of fusion and the heat of crystallization were calculated using the analysis software provided with the instrument. Therefore, the degree of crystallinity is calculated using the following formula: Degree of crystallinity (%) = (((Heat of fusion (J / g) - Heat of crystallization (J / g)) / 140 (J / g)) × 100
[0047] (Method for Determination of Calcium) -Preparation of Test Solution- Accurately weigh 0.05 g of the sample, add 2 mL of sulfuric acid, and let stand for about 20 minutes. Add 2 mL of nitric acid and 1 mL of ultrapure water, and let stand for about 10 minutes. Then, decompose using microwave, dilute the solution to 25 mL as needed, and determine the calcium content using inductively coupled plasma optical emission spectrometry (ICP-OES) manufactured by Thermo Fisher Scientific.
[0048] (Method for Determination of Phosphorus) - Preparation of Test Solution- Accurately weigh 0.05 g of the sample, add 2 mL of sulfuric acid, and let stand for about 20 minutes. Add 2 mL of nitric acid and 1 mL of ultrapure water, and let stand for about 10 minutes. Then, decompose using microwave, dilute the solution to 25 mL as needed, and determine the phosphorus content using inductively coupled plasma optical emission spectrometry (ICP-OES) manufactured by Thermo Fisher Scientific.
[0049] (Example 1) A nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) of 1 part by weight relative to PET resin (SD-R: Zhejiang Jianxin Jiaren New Material Co., Ltd.), an antioxidant (AO-80: ADEKA Co., Ltd.) of 0.2 parts by weight relative to PET resin (100 parts by weight), an antioxidant (PEP-36: ADEKA Co., Ltd.) of 0.3 parts by weight relative to PET resin, and a lubricant (Licocare RBW360: Clariant Japan Co., Ltd.) of 0.3 parts by weight relative to PET resin were added to the PET resin (SD-R: Zhejiang Jianxin Jiaren New Material Co., Ltd.). Then, a pigment (MONARCH 800 Carbon Black: Cabot Corporation) of 1 part by weight relative to PET resin was added. Subsequently, the insert 93 and socket 94, serving as the zipper opening element, are injection molded onto the zipper tape. Then, the degree of crystallinity of the socket 94 is measured according to the method for measuring crystallinity, prior to a high-temperature washing test after injection molding. The measurement results are shown in Table 1.
[0050] (Example 2) To a PET resin (KP-123: PET Refining Technology Co., Ltd.), add 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.), 0.2 parts by weight of an antioxidant (AO-80: ADEKA Co., Ltd.), 0.3 parts by weight of an antioxidant (PEP-36: ADEKA Co., Ltd.), and 0.5 parts by weight of a lubricant (Licocare RBW360: Clariant Japan Co., Ltd.), relative to the PET resin (100 parts by weight). Then, add 2 parts by weight of a pigment (MONARCH 800 Carbon Black: Cabot Corporation). Then, the degree of crystallinity was measured in the same manner as in Example 1. The results are shown in Table 1.
[0051] (Comparative Example 1) Similar to Example 1, a plug 93 and a socket 94 were fabricated, and their crystallinity was measured. The measurement results are shown in Table 1. Furthermore, no pigments for coloring were added, and the product was transparent.
[0052] (Comparative Example 2) 0.5 parts by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) relative to 100 parts by weight of PET resin (SD-R: Zhejiang Jianxin Jiaren New Material Co., Ltd.), 0.2 parts by weight of an antioxidant (AO-80: ADEKA Co., Ltd.), 0.3 parts by weight of an antioxidant (PEP-36: ADEKA Co., Ltd.), and 0.3 parts by weight of a lubricant (Licocare RBW360: Clariant Japan Co., Ltd.) relative to PET resin (SD-R: Zhejiang Jianxin Jiaren New Material Co., Ltd.) were added to PET resin (100 parts by weight). Then, the degree of crystallinity was measured in the same manner as in Example 1. The results are shown in Table 1.
[0053] [Table 1] Degree of crystallinity (%) Example 1 16.69 Example 2 12.00 Comparative Example 1 7.14 Comparative Example 2 10.71
[0054] (Evaluation of Heat Deformation) For Examples 1, 2, and Comparative Examples 1 and 2, washing and drying were performed under the following series of processing conditions. Furthermore, the heat deformation of the plug 93 and socket 94 after washing and after drying was confirmed. The results are shown in Table 2. Moreover, the following conditions are assumed to be for high-temperature washing in Europe.
[0055] -Processing Conditions- 1. Wash at 90℃ for 15 minutes 2. Rinse for 3 minutes 3. Spin dry for 1 minute 4. Dry at 120℃ for 10 minutes
[0056] -Confirmation of Heat Deformation- Regarding Examples 1, 2, and Comparative Examples 1 and 2, the insertion feel when inserting the washed and dried insert 93 into the socket 94 was confirmed. Comparative Example 1 was only washed at 90°C, and as shown in Figure 3, the upper side of the groove 91a of the socket 94 deformed and narrowed. Furthermore, if it was dried at 120°C, as shown in Figure 4, the upper side of the groove 91a of the socket 94 further deformed, becoming almost without gaps, and the resin as a whole became cloudy. As shown in Figures 3 and 4, if the groove 91a deforms and narrows, it becomes impossible to insert the strip into the groove 91a, and the zipper opening and closing operation cannot be performed. On the other hand, although Examples 1 and 2 have some deformation, they do not become impossible to insert the strip into the groove 91a, and the zipper opening and closing function can be maintained. Based on the results of the crystallinity measurement and the confirmation of heat deformation, it was clarified that if the crystallinity is 12% or more, the zipper opening and closing operation can be performed even after washing and drying.
[0057] As described in the embodiments and examples, using zipper components with increased crystallinity immediately after manufacturing with a nucleating agent (before high-temperature washing and drying) is a crucial technique for effectively utilizing PET material. However, during extensive verification of the additive combinations described in the embodiments, the inventors discovered that certain additive combinations resulted in the injection-molded components turning gray. If this discoloration occurs, the components cannot be colored as intended for the zipper product. While this has little impact when the zipper is black, it results in defective products when white or light-colored. Even with other color schemes, the overall zipper tone is inconsistent, leading to further defects. Therefore, the inventors investigated the cause and conducted further experiments and verifications to prevent this defect. Details of these experiments and verifications will be described later, but the conclusion is that the graying is caused by the coexistence of antimony as a polymerization catalyst in the PET resin used as the material, along with phosphorus-based antioxidants and nucleating agents. It is speculated that the graying occurs due to the interaction between antimony and phosphorus-based antioxidants, with the graying process being promoted by the nucleating agent. Furthermore, the phosphorus content of the phosphorus-based antioxidant in the resin composition can be calculated based on the ratio of the content of the (C2) secondary antioxidant to the phosphorus in the phosphorus-based antioxidant. Specifically, it is speculated that the phosphorus content in the resin composition is in the range of approximately 50 ppm to 5000 ppm. For example, when using a phosphorus-based antioxidant (PEP-36: ADEKA Corporation) as the (C2) secondary antioxidant, the phosphorus-based antioxidant is typically used in a range of 0.1 parts by weight to 5 parts by weight relative to 100 parts by weight of resin. In this case, the phosphorus content in the resin composition is approximately 93 ppm to 4650 ppm. In addition, when the content of phosphorus-based antioxidant (PEP-36: ADEKA Corporation) is typically used in the range of 0.3 parts by weight to 1 part by weight relative to 100 parts by weight of resin, the phosphorus content in the resin composition is approximately 280 ppm to 933 ppm.
[0058] Based on the aforementioned speculation, a solution was derived: simply avoid manufacturing zippers using specific additive combinations as described above. However, in this solution, due to the limited freedom of material selection during zipper manufacturing, it would be more ideal to suppress graying of PET resin injection-molded parts regardless of the combination with any antioxidant. Regarding this aspect, the inventors, through repeated and extensive experiments and verifications, successfully obtained insights as a countermeasure. Specifically, they discovered that adding a calcium-containing lubricant can suppress the aforementioned undesirable graying. By obtaining this insight, the practical application of PET resin in resin injection-molded parts of zippers was achieved more generally. The causes of graying and the experiments and verifications leading to the countermeasures will be explained below.
[0059] The verification of the cause of graying of PET resin after injection molding will be explained using Reference Examples 1 to 5. (Reference Example 1) In a PET resin (KP-123: PET REFINE TECHNOLOGY Co., Ltd.) using antimony as a polymerization catalyst, 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) relative to 100 parts by weight of PET resin, 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.) relative to PET resin, and 0.3 parts by weight of a phosphorus antioxidant (PEP-36: ADEKA Co., Ltd.) relative to PET resin were added. Then, the zipper tape was injection molded in the form of a plug 93 and a socket 94 as the opening element of the zipper. A photograph of the resulting plug 93 and socket 94 is shown in Figure 5.
[0060] (Reference Example 2) In a PET resin (KP-123: PET REFINE TECHNOLOGY Co., Ltd.) using antimony as a polymerization catalyst, a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) of 1 part by weight relative to the PET resin (100 parts by weight) and a phosphorus-based antioxidant (PEP-36: ADEKA Co., Ltd.) of 0.3 parts by weight relative to the PET resin were added. Then, the mixture was injection molded into the zipper tape in the form of a pusher 93 and a socket 94, which are the opening components of the zipper. A photograph of the resulting pusher 93 and socket 94 is shown in Figure 6.
[0061] (Reference Example 3) In a PET resin (KP-123: PET REFINE TECHNOLOGY Co., Ltd.) using antimony as a polymerization catalyst, a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) of 1 part by weight relative to the PET resin (100 parts by weight) and a phenolic antioxidant (AO-80: ADEKA Co., Ltd.) of 0.2 parts by weight relative to the PET resin were added. Then, the mixture was injection molded into the zipper tape in the form of a pusher 93 and a socket 94, which are the opening components of the zipper. A photograph of the resulting pusher 93 and socket 94 is shown in Figure 7.
[0062] (Reference Example 4) In a PET resin (KP-123: PET REFINE TECHNOLOGY Co., Ltd.) using antimony as a polymerization catalyst, 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.) and 0.3 parts by weight of a phosphorus antioxidant (PEP-36: ADEKA Co., Ltd.) relative to the PET resin (100 parts by weight) were added. Then, the resulting insert 93 and socket 94 were injection molded into the zipper tape as zipper opening components. A photograph of the resulting insert 93 and socket 94 is shown in Figure 8.
[0063] (Reference Example 5) In a PET resin (TRN-8550FF: Teijin Co., Ltd.) using titanium as a polymerization catalyst (but not antimony), 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.), 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.), and 0.3 parts by weight of a phosphorus antioxidant (PEP-36: ADEKA Co., Ltd.) relative to the PET resin (100 parts by weight) were added. Then, the resulting insert 93 and socket 94 were injection molded into the zipper tape as zipper opening components. A photograph of the resulting insert 93 and socket 94 is shown in Figure 9.
[0064] In Reference Examples 1 to 5, no pigment was added for ease of understanding of the graying process. Therefore, the injected rod 93 and socket 94 were injected in a transparent state unless any particular abnormality occurred. Furthermore, white zipper tape was used. Moreover, no lubricant was prepared in Reference Examples 1 to 5.
[0065] As can be seen from Figures 5 to 9, the resin of the plug 93 and socket 94 in Reference Examples 3, 4, and 5 is not grayed out but becomes transparent. On the other hand, the front end or edge of the plug 93, the entire base of the socket 94, and the edge of the socket rod in Reference Example 1 are discolored to black. In Reference Example 2, although it is not grayed out like in Reference Example 1, it is clear from the comparison with Reference Examples 3 to 5 that the front end or edge of the plug 93, the entire base of the socket 94, and the edge of the socket rod are discolored to light black.
[0066] Furthermore, regarding Reference Example 2, the resin was injected immediately after injection molding began in a colorless and transparent state. However, after approximately five injections of the insert 93 and socket 94, the tendency to gradually darken increased. It is presumed that this is because, over time, heat is applied to the synthetic resin stored in the injection cylinder of the injection molding machine, thereby causing graying. This tendency is also visible in Reference Example 1 shown in Figure 5, where the longer the residence time in the injection cylinder, the darker the gray becomes. Furthermore, the photograph of Reference Example 2 in Figure 6 shows the state after the eighth injection molding. On the other hand, regarding Reference Examples 3 to 5, no signs of graying were observed even after repeated injection molding. In particular, the only difference between Reference Example 3 and Reference Example 1 is the absence of a phosphorus-based antioxidant, thus it is understood that the presence or absence of a phosphorus-based antioxidant affects the occurrence of graying. In addition, the only difference between Reference Example 4 and Reference Example 1 is the absence of a nucleating agent, thus it is understood that the presence or absence of a nucleating agent affects the occurrence of graying. In addition, the difference between Reference Example 5 and Reference Example 1 is that the PET resin is a PET resin that does not use antimony as a polymerization catalyst. Therefore, it can be understood that the use of antimony in the polymerization catalyst will affect the occurrence of graying.
[0067] Based on the results of the above Reference Examples 1 to 5, it can be seen that the coexistence of antimony as a polymerization catalyst, phosphorus-based antioxidants, and crystal nucleating agents in the PET resin used as a material is the cause of graying.
[0068] As described above, certain conclusions have been reached regarding the causes of graying, leading to a solution: zippers can be manufactured by avoiding specific combinations of resins and additives as described above (combinations of PET resin using antimony as a polymerization catalyst with phosphorus-based antioxidants and nucleating agents). However, during repeated and extensive testing and verification, it was found that even this specific combination of resins and additives can suppress graying. Specifically, it was clarified that adding calcium-containing additives (e.g., calcium salt lubricants) can suppress the aforementioned undesirable graying condition.
[0069] The following description uses Example 3 and Comparative Example 3. Furthermore, Example 3 is an example in which a calcium-containing lubricant was added, compared to Reference Example 1. On the other hand, Comparative Example 3 is an example in which a calcium-free lubricant was added, compared to Reference Example 1.
[0070] (Example 3) In a PET resin (KP-123: PET Refining Technology Co., Ltd.) using antimony as a polymerization catalyst, 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) relative to 100 parts by weight of the PET resin (1 part by weight), 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.) relative to the PET resin, 0.3 parts by weight of a phosphorus antioxidant (PEP-36: ADEKA Co., Ltd.) relative to the PET resin, and 0.5 parts by weight of a calcium-containing lubricant (Licocare RBW360: Clariant Co.) relative to the PET resin were added. Then, the mixture was injection molded into a zipper tape in the form of an insert 93 and a socket 94, which are the opening components of the zipper. The resulting photographs of the plug 93 and socket 94 are shown on the left side of Figure 10. Furthermore, in this figure, to facilitate understanding of the changes after adding lubricant compared to before adding lubricant, photographs related to Reference Example 1 are arranged on the right side of Figure 10.
[0071] Subsequently, the calcium content of socket 94 was determined according to the method for determining calcium. The calcium content was 180 ppm.
[0072] (Comparative Example 3) In a PET resin (KP-123: PET Refining Technology Co., Ltd.) using antimony as a polymerization catalyst, 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.), 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.), 0.3 parts by weight of a phosphorus-based antioxidant (PEP-36: ADEKA Co., Ltd.), and 0.5 parts by weight of a calcium-free lubricant (Licomont NAV101: Clariant Co.) were added. The mixture was then injection molded into a zipper tape in the form of a pusher 93 and a socket 94, which serve as the opening element of the zipper. A photograph of the resulting plug 93 and socket 94 is shown on the left side of Figure 11. Furthermore, in this figure, to facilitate understanding of the changes after adding lubricant compared to before adding lubricant, photographs related to Reference Example 1 are arranged on the right side of Figure 11.
[0073] Similar to Reference Examples 1 to 5, no pigment is added for ease of understanding of the graying process. Therefore, the injected rod 93 and socket 94 are injected in a transparent state unless any particular abnormality occurs. Additionally, white zipper tape is used.
[0074] As shown in Figure 10, the plug 93 and socket 94, with the addition of a calcium-containing lubricant, did not turn gray and remained transparent. However, as shown in Figure 11, when a calcium-free lubricant (sodium-based lubricant) was added, the plug 93 and socket 94 still turned gray, but compared to the case without lubricant (reference example 1 on the right side of Figure 11), although a slight graying occurred, it was a light gray.
[0075] Subsequently, in order to further verify the graying status when the amount of calcium-containing lubricant (Licocare RBW360: Clariant) added was varied, the following tests were conducted in Example 4, Example 5, Reference Example 6, Reference Example 7 and Reference Example 8.
[0076] (Example 4) In a PET resin (KP-123: PET Refining Technology Co., Ltd.) using antimony as a polymerization catalyst, 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) was added relative to 100 parts by weight of the PET resin (1 part by weight of the PET resin), 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.) relative to the PET resin, 0.3 parts by weight of a phosphorus antioxidant (PEP-36: ADEKA Co., Ltd.) relative to the PET resin, and 0.2 parts by weight of a calcium-containing lubricant (Licocare RBW360: Clariant Co., Ltd.) relative to the PET resin. Then, resin injection molding was performed to produce a resin composition. The calcium content of the obtained resin composition was determined according to the calcium determination method. The calcium concentration was measured at 78 ppm. Visual inspection of the resin composition of Example 4 showed no graying. Furthermore, PEP-36 (Adekastab), manufactured by ADEKA Corporation and used as a phosphorus-based antioxidant, has the molecular formula C35H54O6P2 and a molecular weight of 633. Therefore, the phosphorus concentration in the resin composition is approximately 280 ppm.
[0077] (Example 5) The resin composition was prepared in the same manner as in Example 4, except that 0.1 parts by weight of a calcium-containing lubricant (Licocare RBW360: Clariant) was added relative to the PET resin. The calcium content of the obtained resin composition was determined according to the calcium determination method. The calcium content was 39 ppm. Visual inspection of the resin composition of Example 5 showed no graying.
[0078] (Reference Example 6) The resin composition was prepared in the same manner as in Example 4, except that 0.05 parts by weight of a calcium-containing lubricant (Licocare RBW360: Clariant) was added relative to 100 parts by weight of the PET resin. The calcium content of the obtained resin composition was determined according to the method for determining calcium. The calcium content was 19.5 ppm. Visual inspection of the resin composition of Reference Example 6 revealed that although it was light gray, it had undergone some graying.
[0079] (Reference Example 7) The resin composition was prepared in the same manner as in Example 4, except that 0.01 parts by weight of a calcium-containing lubricant (Licocare RBW360: Clariant) was added relative to 100 parts by weight of the PET resin. The calcium content of the obtained resin composition was determined according to the method for determining calcium. The calcium content was 3.9 ppm. Visual inspection of the resin composition of Reference Example 7 revealed a slightly darker graying color compared to Reference Example 6.
[0080] (Reference Example 8) In a PET resin (KP-123: PET Refining Technology Co., Ltd.) using antimony as a polymerization catalyst, 1 part by weight of a crystallizing nucleating agent (HIMILAN 1707: Mitsui Dow Polychemical Co., Ltd.) relative to 100 parts by weight of the PET resin (1 part by weight), 0.2 parts by weight of a phenolic antioxidant (AO-80: ADEKA Co., Ltd.) relative to the PET resin, and 0.3 parts by weight of a phosphorus antioxidant (PEP-36: ADEKA Co., Ltd.) relative to the PET resin were added (without adding a calcium-containing lubricant). Then, resin injection molding was performed to produce a resin composition. Visual inspection of the resin composition of Reference Example 8 revealed a graying effect, which was darker and closer to black than that of Reference Example 7.
[0081] Based on the test results of Examples 4, 5, 6, 7, and 8 above, it can be confirmed that even with the specific combination of the resin and the specific additives, if the calcium content is not at least 20 ppm, graying cannot be suppressed; if it is 20 ppm or more, the degree of graying will remain light gray. It can also be confirmed that the calcium content is preferably 39 ppm or more, and more preferably 78 ppm or more.
[0082] Based on the results of all the above-described tests, it can be understood that the graying phenomenon of injection-molded resin caused by the coexistence of antimony as a polymerization catalyst, phosphorus-based antioxidants, and nucleating agents in the manufacture of PET resin as a material can be suppressed by further adding calcium-containing additives. Furthermore, the calcium-containing additive does not necessarily need to be a lubricant; it can be an additive other than a lubricant. It can also be a mixture of a calcium-free lubricant and another calcium-containing additive. Among these, the lubricant has various effects in addition to suppressing graying during injection molding; therefore, a calcium-containing lubricant is preferred.
[0083] When clothing is manufactured using the zipper of the present invention, since the clothing using the zipper of the present invention is an environmentally friendly product that reuses recycled PET resin, and can be sold as clothing labeled with a label that can be washed at high temperatures of 90°C or higher, which can attract consumers' attention, it is beneficial to both sellers and buyers.
[0084] Furthermore, the present invention is not limited to the described embodiments, but can also be adapted to utilize technologies that are substantially the same as or have the same effect as the technologies described in the embodiments of the present invention and that are known to those skilled in the art, or can be used as alternative technologies, or can be added in an additional manner. [Simplified Explanation of the Diagram]
[0085] Figure 1 is a diagram showing the general form of a zipper (a zipper with a lower stop) having a component manufactured by resin injection molding, and is a diagram showing the appearance of the zipper in an embodiment of the present invention. Figure 2 is a diagram showing the general form of a zipper (a zipper with an opening member) having a component manufactured by resin injection molding, and is a diagram showing the appearance of the zipper in an embodiment of the present invention. Figure 3 is a diagram showing the upper side of the groove 91a of the socket 94 after washing at 90°C, which has become narrower due to deformation. Figure 4 is a diagram showing the upper side of the groove 91a of the socket 94 after drying at 120°C, which has further deformed and the resin as a whole has become cloudy. Figure 5 is a photograph showing the state of the insert 93 and socket 94 after injection molding according to Reference Example 1. Figure 6 is a photograph showing the state of the insert 93 and socket 94 after injection molding according to Reference Example 2. Figure 7 is a photograph showing the state of the insert 93 and socket 94 after injection molding according to Reference Example 3. Figure 8 is a photograph showing the injection-molded plug 93 and socket 94 of Reference Example 4. Figure 9 is a photograph showing the injection-molded plug 93 and socket 94 of Reference Example 5. Figure 10 is a photograph comparing the injection-molded plug 93 and socket 94 of Example 3 with Reference Example 1. Figure 11 is a photograph comparing the injection-molded plug 93 and socket 94 of Comparative Example 3 with Reference Example 1.
Claims
1. A zipper having teeth installed at the edge of the zipper tape, the zipper having a resin injection component formed by injection molding a synthetic resin containing polyethylene terephthalate as a main component onto the zipper tape, the synthetic resin of the resin injection component containing a crystallizing nucleating agent, the degree of crystallinity of the resin injection component being 12% or more, the resin injection component being a component made of a synthetic resin that will not become a combination of polyethylene terephthalate resin using antimony as a polymerization catalyst, a phosphorus-based antioxidant, and a crystallizing nucleating agent.
2. The zipper as described in claim 1, wherein, The resin injection component is any one or a combination of any number of zipper teeth, lower stop, upper stop, insert, and socket.
3. The zipper as described in claim 2, wherein, The resin injection component is a plug or socket, and a resin film is provided on the zipper tape adjacent to the plug or socket.
4. The zipper as described in claim 1 or 2, wherein, The resin injection component is a component manufactured by injecting it into a mold at a temperature not exceeding 30°C.
5. A zipper having teeth installed at the edge of the zipper tape, the zipper having a resin injection component formed by injection molding a synthetic resin containing polyethylene terephthalate as a main component onto the zipper tape, wherein, when the total amount of the synthetic resin in the resin injection component is set to 100% by weight, the synthetic resin contains more than 50 ppm of phosphorus and more than 20 ppm of calcium.
6. The zipper as described in claim 5, wherein, The synthetic resin contains a lubricant in which calcium is present.
7. The zipper as described in claim 1 or 5, wherein, The polyethylene terephthalate used as the synthetic resin comprises recycled polyethylene terephthalate.
8. A garment characterized by using a zipper as described in claim 1 or 5, thereby enabling high-temperature washing at temperatures above 90°C.
